Sistem Informasi Perizinan Santri Online pada Pondok Pesantren Modern Darul Ihsan Berbasis Web - Agung, Agung Prayoga; Ikhwan, Ali (Jurnal Ilmiah Sains dan Teknologi, 2024)
Scientific development today is developing very rapidly especially in the field of IT is a necessary area of society to maximum convenience and optimum results. In the neighborhood of the Modern Pondok Pesantren Darul Ihsan the licensing system is still done manually and is not computerized. Besides, the governor repeatedly applied for permission but not on the permission schedule. So from that, we need some kind of web-based online licensing system to help work the privacy and security parts. In this article, the author uses the Waterfall method, which is a method of developing a system or software where the work process of the system is run sequentially and systematically. This online licensing system is expected to help the central guardian in the license process and speed up the licencing process to make it easier.